2015
DOI: 10.1007/s00210-015-1151-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone, a synthetic glucocorticoid, on human periodontal ligament stem cells

Abstract: Recent studies have showed that psychosocial stress causes elevated secretion of cortisol, the principal glucocorticoid (GC), and thus increases the extent of periodontal breakdown. In this study, we investigated whether stress-associated periodontal disturbance may be due to GC-induced changes in the periodontal ligament stem cells (PDLSCs), one of the most promising candidates for periodontal tissue regeneration. Our results in this study showed that dexamethasone (Dex) treatment causes the translocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…Data from ELISA (n=3) also showed that the concentration of DKK1 in the DP conditioned medium is increased in response to Dex (Figure E). These results are consistent with those obtained in previous studies that reported an increase in DKK1 expression in osteoblasts and periodontal ligament stem cells treated with Dex . Furthermore, RU486, a synthetic GR antagonist, significantly attenuated Dex‐induced DKK1 mRNA expression in DP cells (n=3; Figure F,G), demonstrating that Dex‐induced DKK1 expression is GR dependent.…”
Section: Resultssupporting
confidence: 92%
“…Data from ELISA (n=3) also showed that the concentration of DKK1 in the DP conditioned medium is increased in response to Dex (Figure E). These results are consistent with those obtained in previous studies that reported an increase in DKK1 expression in osteoblasts and periodontal ligament stem cells treated with Dex . Furthermore, RU486, a synthetic GR antagonist, significantly attenuated Dex‐induced DKK1 mRNA expression in DP cells (n=3; Figure F,G), demonstrating that Dex‐induced DKK1 expression is GR dependent.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, the organized spindle shape of fibroblasts demonstrated in the current interval of the treated group was also recorded by other researchers' in vitro studies 27,31 . However, the herein results of the treated group were not in accordance with Choi et al, as they reported that dexamethasone treatment induced the production of DKK-1 gene by periodontal ligament stem cells in vitro which in turn inhibited the growth of human periodontal ligament stem cells 17 .…”
Section: Discussioncontrasting
confidence: 75%
“…Experimental work considers rat successful animal model is for being easily manipulated and a for obtaining similar tissues to the human body 15 and different researches on dexamethasone effect used rats as the model of choice. 2,16 The use of dexamethasone periodontal tissue was studied in different in vitro experiments [17][18] and in vivo available research work dealt with the drug action as repeated injectable doses or as a topical application. 4,19,20 Tooth luxation can be induced by trauma, infection, periodontitis, malocclusion or undue orthodontic force application.…”
Section: Discussionmentioning
confidence: 99%
“…hDPCs were plated in 8-chamber slides (SPL, Korea) at a density of 2 × 10 3 cells per well and cultured in serum-free medium in the presence of DHT or vehicle control (methanol) for 5 h. Immunofluorescence staining of AR was performed as previously described [ 36 ]. Briefly, proteins were immunolabeled by incubating with anti-AR antibody (1:100, Cell Signaling Technology), anti-CRTH2/DP2 antibody (1:100, Novus) and anti-rabbit Alex Fluor 488 conjugated antibody (1:200; Invitrogen, OR, USA).…”
Section: Methodsmentioning
confidence: 99%